Investigation of the Therapeutic Contribution of the Nanoconjugated Form Using Sono-Photochemical Application; Novel Indium Phthalocyanine and Its Cystein-Functionalized Graphene Quantum Dot Derivative - Celep, Kevser; Gokcil, Gokce; Sen, Pinar; Sahin, Fikrettin; Erdogmus, Ali; Atmaca, Goknur Yasa (WILEY, 2025)
This study aimed to synthesize sensitizer molecules with high therapeutic efficacy using a new indium phthalocyanine (InPc) with halogen substituents and novel supramolecular hybrids containing graphene quantum dots (GQDs). 4-Tetra-(2-bromo-4-methylphenol) phtalocyaninato indium(III) chloride was immobilized via pi-pi stacking interaction on GQDs functionalized with cysteine. The photochemical and sono-photochemical features were determined for both indium phthalocyanine alone and its respective conjugate to investigate their potential in advanced cancer therapies with enhanced singlet oxygen generations. The nanoconjugate form of InPc demonstrated better singlet oxygen quantum yields with results reaching to Phi triangle(SPDT) = 1.31 and Phi triangle(PDT) = 0.81 as compared to the InPc alone. These results also confirm that sono-photochemical method enhances therapeutic activity due to the combined benefits of light an ultrasound. This study paves the way for future research aimed at achieving highly efficient singlet oxygen generation.
Keywords: graphene-quantum dots; indium phthalocyanine; photosensitizer; singlet oxygen; sono-photochemical; PHOTODYNAMIC THERAPY; ZINC PHTHALOCYANINE; IN-VITRO; RECENT PROGRESS; CANCER; EFFICACY; NANOTECHNOLOGY; LUMINESCENCE; FLUORESCENCE; PHENOXY; Chemistry